2009
DOI: 10.2134/agronj2009.0103
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Zinc‐Efficient Wheat Genotypes with High Grain Yield Using a Stress Tolerance Index

Abstract: There is no reliable indicator for identifying Zn‐deficiency tolerant genotypes with high grain yield. The aim of this investigation was to compare the grain yield response of 30 spring and 20 winter bread wheat (Triticum aestivum L.) genotypes to Zn fertilization under field condition and to select high grain yield Zn‐deficiency tolerant genotypes using a stress tolerance indicator. The stress tolerance indicator is a stress tolerance index (STI) used to identify genotypes that produce high yields under both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
0
14
1
Order By: Relevance
“…Wheat is the staple food for people living in northern China and reliance on grain with low Zn concentrations can result in chronic Zn deficiency and its associated health problems (Cakmak et al, 1999; Yang et al, 2007; Zhang et al, 2010). Human Zn deficiency has become a significant issue in China and elsewhere, arousing great concern among agronomists and nutritionists (Ma et al, 2008; Khoshgoftarmanesh et al, 2009; Shi et al, 2010; Prom‐u‐thai et al, 2010; Grant et al, 2010; Cakmak, 2010).…”
mentioning
confidence: 99%
“…Wheat is the staple food for people living in northern China and reliance on grain with low Zn concentrations can result in chronic Zn deficiency and its associated health problems (Cakmak et al, 1999; Yang et al, 2007; Zhang et al, 2010). Human Zn deficiency has become a significant issue in China and elsewhere, arousing great concern among agronomists and nutritionists (Ma et al, 2008; Khoshgoftarmanesh et al, 2009; Shi et al, 2010; Prom‐u‐thai et al, 2010; Grant et al, 2010; Cakmak, 2010).…”
mentioning
confidence: 99%
“…Daneshbakhsh et al (2013) reported enhanced phytosiderophore exudation by addition of Zn to Kavir was associated with lower uptake of Fe. In the previous experiments, Kavir was categorized as a Zn-inefficient wheat cultivar, while Rushan was reported to be a Zn-efficient cultivar (Khoshgoftarmanesh et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Plant cultivation Seeds of the wheat cultivar 'Back Cross (BC) Rushan' were used (Seed and Plant Improvement Institute (SPII), Karaj, Iran [31] ). The plants were germinated on filter paper for 5 days and then hydroponically grown for three weeks in a greenhouse at a 24-14 8C day-night cycle with 16 4 and 0.2 mM ZnSO 4 ) was used, buffered with 2.5 mM 3-(N-morpholino)propanesulfonic acid (MOPS) and adjusted with 1 M NaOH to a pH between 6.5 and 6.9.…”
Section: Plant Experimentsmentioning
confidence: 99%